Study of Coconut Farming in Supporting Farmers’ Income in Kambowa District, North Buton Regency - Mawari Mawari; Lely Ersilya (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2023)
Coconut farming research was carried out with the aim of knowing the production process of coconut farming and the amount of its contribution to supporting farmers' income in Kambowa District. This study uses a survey method which is intended to find out the truth conceptually and practically realistically regarding coconut farming in supporting farmers' income. Sampling used the Simple Random Sampling method with homogeneous population limits so that the sample totaled 40 respondents or 10% of the total population of 400 heads of households who carry out coconut farming. Collecting data using observation techniques, questionnaires, interviews and documentation. Data analysis used descriptive quantitative analysis with frequency tables and calculations that only reached the percentage level. Coconut farming is carried out by farmers in a simple way on large areas of land using manual tools and technology, own capital and a small amount of labor, starting from land preparation to post-harvest. The results of coconut farming in Kambowa District average IDR 6,092,500/Ha and these results can provide a significant contribution of 34.72% in supporting farmers' income.